Alzheimer's disease medication use and adherence patterns by race and ethnicity. Issue 4 (8th August 2022) - Olchanski, Natalia; Daly, Allan T.; Zhu, Yingying; Breslau, Rachel; Cohen, Joshua T.; Neumann, Peter J.; Faul, Jessica D.; Fillit, Howard M.; Freund, Karen M.; Lin, Pei‐Jung
Abstract: Background: We examined racial and ethnic differences in medication use for a representative US population of patients with Alzheimer's disease and related dementias (ADRD). Methods: We examined cholinesterase inhibitors and memantine initiation, non‐adherence, and discontinuation by race and ethnicity, using data from the 2000–2016 Health and Retirement Study linked with Medicare and Medicaid claims. Results: Among newly diagnosed ADRD patients (n = 1299), 26% filled an ADRD prescription ≤90 days and 36% ≤365 days after diagnosis. Among individuals initiating ADRD‐targeted treatment (n = 1343), 44% were non‐adherent and 24% discontinued the medication during the year after treatment initiation. Non‐Hispanic Blacks were more likely than Whites to not adhere to ADRD medication therapy (odds ratio: 1.50 [95% confidence interval: 1.07–2.09]). Discussion: Initiation of ADRD‐targeted medications did not vary by ethnoracial group, but non‐Hispanic Blacks had lower adherence than Whites. ADRD medication non‐adherence and discontinuation were substantial and may relate to cost and access to care. HIGHLIGHTS: Initiation of anti‐dementia medications among newly diagnosed Alzheimer's disease and related dementias (ADRD) patients was low in all ethnoracial groups. ADRD medication non‐adherence and discontinuation were substantial and may relate to cost and access to care. Compared to Whites, Blacks and Hispanics had lower use, poorer treatment adherence, and more frequent discontinuation of ADRD medication, but when controlling for disease severity and socioeconomic factors, racial disparities diminish. Our findings demonstrate the importance of adjusting for socioeconomic characteristics and disease severity when studying medication use and adherence in ADRD patients.